2009
DOI: 10.1038/nnano.2009.265
|View full text |Cite|
|
Sign up to set email alerts
|

Anticipating the perceived risk of nanotechnologies

Abstract: Understanding emerging trends in public perceptions of nanomaterials is critically important for those who regulate risks. A number of surveys have explored public perceptions of their risks and benefits. In this paper we meta-analyse these surveys to assess the extent to which the following four hypotheses derived from previous studies of new technologies might be said to be valid for nanotechnologies: risk aversion will prevail over benefit appreciation; an increase in knowledge will not result in reduced av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
149
1
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 209 publications
(158 citation statements)
references
References 59 publications
7
149
1
1
Order By: Relevance
“…7 Specifically, being male, young, white, educated, familiar with nanotechnologies and trusting of regulators have all been linked to lower risk perception of nanotechnologies. 7 However, we are unaware of any publication that has examined the perceptions of nanomaterials and chemicals in the manner described in this study. In this study, we found that, overall, the general public perceives chemicals as riskier than nanomaterials, with the exception of their use in medicines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Specifically, being male, young, white, educated, familiar with nanotechnologies and trusting of regulators have all been linked to lower risk perception of nanotechnologies. 7 However, we are unaware of any publication that has examined the perceptions of nanomaterials and chemicals in the manner described in this study. In this study, we found that, overall, the general public perceives chemicals as riskier than nanomaterials, with the exception of their use in medicines.…”
Section: Discussionmentioning
confidence: 99%
“…7 Australian regulators of nanomaterials have suggested that nanomaterials should be framed as chemicals. [8][9][10] It is important to determine the consequences that this framing may have on public perceptions.…”
Section: • Australian Pesticides and Veterinary Medicinesmentioning
confidence: 99%
“…2 Research on ethical, legal, and social issues is vital to understanding how to create social and environmental value in the development of science and technology (e.g., see Hamlett et al 2008;Pidgeon et al 2009a, b;Satterfield et al 2009;Scheufele and Corley 2008;Corley and Scheufele 2010), which includes development of processes to address the diversity of views across different publics.…”
Section: Make Moral Progressmentioning
confidence: 99%
“…2). A meta-analysis of 22 public surveys conducted from 2002 to 2009 in the United States, Canada, Europe, and Japan found ongoing low levels of public familiarity with nanotechnology, with benefits viewed as outweighing risks by 3 to 1, but also a large (44%) minority who had not yet made up their minds about benefits or risks (Satterfield et al 2009). …”
Section: Nanotechnology Innovation and Commercializationmentioning
confidence: 99%
“…Develop operational aspects of anticipatory and participatory governance (e.g., Roco, 2008;Barben et al 2008;Satterfield et al 2009;Sclove, 2010) Transition from a research-centric to a demand/user/application-centric focus J Nanopart Res -Support access of industry to data bases, research projects, user facilities and international collaboration -Provide education and supporting tolls for the introduction of nanotechnology for economical benefit and better paying jobs, to increase penetration of nanotechnology in both emerging and traditional industries.…”
Section: Study Changing Societal Interactions Due To Converging and Ementioning
confidence: 99%